Instilling Religious Character Values Based on P2KK at the University of Muhammadiyah Malang - Ummami, Farida; Faridi, Faridi; Nurhakim, Moh. (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study discusses the challenges in facing the phenomenon of globalization that can cause negative impacts, for example, weak faith, poor morals, and commendable morals in students. The main objective of this study is to explain the instillation of religious character values based on P2KK at the University of Muhammadiyah Malang. This study uses a qualitative research approach with a case study analysis type. Data collection techniques are carried out through observation, interview and documentation techniques. Research data taken through interviews in the form of words, voice notes, written documentation of interviews and written event reports. The results of the study show (1) P2KK at the University of Muhammadiyah Malang is designed to equip new students with religious values based on Islamic teachings and Muhammadiyah (2) P2KK at the University of Muhammadiyah Malang instills religious character values in students through an approach based on Al-Ghazali's thoughts, which emphasize worship, sincerity, discipline, and responsibility (3) P2KK activities at the University of Muhammadiyah Malang have a positive impact on the development of students' religious character. This program instills values such as discipline, responsibility, tolerance, and protecting the environment, which are implemented in academic and daily life.